(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The study aimed to identify the leadership requirements to activate the Green Schools Initiative and to identify the most prominent challenges facing leaders to achieve the leadership requirements of green schools and to propose measures to support leaders to achieve the leadership requirements of green schools. The study used the descriptive analytical approach, by analyzing ten studies. The study concluded that there are central, local and school leadership requirements to activate the initiative. The most prominent central requirements are that the general administration provides educational programs that contribute to caring for the school environment and its resources and including environmental issues and green school content in the curricula. As for the local requirements, they are represented in preparing guides for schools to achieve the green school standards and coordinating with local councils to improve the internal and external environment of schools. The school requirements include involving parents of students and members of the local community in the environmental programs and projects of green schools, preparing annual reports on the level of progress in achieving the green school standards, and that among the most important challenges are the weak material and moral appreciation of teachers and school workers to perform these tasks and the lack of sufficient spaces and spaces in schools practicing these activities. The study proposed several measures to overcome these challenges, including interest in preparing cadres and leaders. For the future, it works according to systematic plans to achieve sustainability, provide the necessary training for all students and school staff, taking into account choosing appropriate times and places for training and holding art exhibitions to document the achievements of this initiative.